Tell me everything you don't remember : the stroke that changed my life - Lee, Christine Hyung-Oak (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2017)
A book-length expansion of the author's viral Buzzfeed essay traces her efforts to rebuild and reclaim her life after a stroke at the age of 33, tracing her recapture of everyday skills and memories from her early childhood and marriage.
Keywords: Lee, Christine Hyung-Oak.; Cerebrovascular disease -- Patients -- Biography